MENGEMBANGKAN KREATIVITAS ANAK MELALUI KEGIATAN MENGGAMBAR DI RA DARUL HUDA MATARAM BARU - Ardiyansyah, Ahmad (LPPM STAI DARUSSALAM LAMPUNG, 2020)
Abstract The purpose of the study was to develop the artistic development ability of age 5-6 at RA Darul Huda Mataram Baru, East Lampung. This study used an action research method consisting of 2 cycles involving 15 children. The cycle in this research is in the form of planning, action, observation, and reflection. Previously, the researcher conducted a pre-action research to determine the early ability of children's artistic development in free drawing activities. To achieve children's development, especially art can be done with fun activities for children. Activities can be done by taking the child out of the room to see directly, what is seen by the child, it can make it easier for the child to remember something. Children are given motivation in remembering and provide opportunities for children to ask questions directly to make children enthusiastic in learning, so in this research, it is explained that the artistic development of group B students is greatly improved, with this the results can be seen from the final score of the research in cycle I and cycle II. The data obtained in the first cycle there are 8 children (53.33%) can draw freely well, and 7 children (46.67%) cannot draw freely well. In the second cycle, data obtained from 13 children (86.67%) can draw freely and 2 children (13.33%) cannot Keywords : Practice, Order, Moral Educatio,Moral Education